Could we suspect pulmonary veno-oclussive disease with a cardiopulmonary exercise test?. (25th November 2020) - Perez Olivares Delgado, C; Segura De La Cal, T; Flox, A; Prudencio, V; Cristo, M.J; Coronel, L; Arribas, F; Escribano, P
Abstract: Background: Cardiopulmonary exercise test (CPET) provides information about the pathophysiology of the exercise limitation. CPET parameters in pulmonary arterial hypertension (PAH) exhibit distinctive features, such as low peak oxygen uptake (pVO2), low end tidal carbon dioxide tension (PetCO2) and high ventilation-carbon dioxide slope (VE/VCO2).Pulmonary veno-oclussive disease (PVOD) is a PAH subgroup with particular underlying physiology, difficult diagnosis and poor prognosis. Purpose: We hypothesized that different CPET patterns could be identified in PAH subgroups, and this may contribute to their diagnosis workup. Methods: CPETs performed on the following PAH subgroups between September 2019 and January 2020 were prospectively included: Idiopathic PAH (IPAH), Heritable PAH (HPAH), and PAH responders to calcium channel blockers (CCB-R). Due to its low prevalence and its clinical relevance, CPET data on PVOD patients was retrospectively included. Results: 57 CPET were included: 20 IPAH (35%); 13 HPAH (22.8%); 9 CCB-R (15.8%), 15 PVOD (26.3%). All patients presented impaired functional capacity with reduced peakVO2 and increased VE/VCO2). Remarkably, PVOD patients, in spite of a younger age, exhibit the worst functional capacity and ventilatory efficiency even showing downward PetCO2 kinetics. CCB-R group achieved the highest peakVO2 and had better ventilatory parameters.(Table 1) Conclusion: CPET is a useful tool to classify patients by PAH subgroups. Very low PetCO2 at rest and a downward PetCO2 kinetic strongly suggest PVOD, which has significant implications on treatment. Funding Acknowledgement: Type of funding source: None